The Endoscopic Hemi-Transseptal Approach to the Sella Turcica: Operative Technique and Case-Control Study - Tewfik, Marc A. (J Neurol Surg B Skull Base, 2014)
Background The hemi-transeptal (Hemi-T) approach was developed to facilitate a binasal two-surgeon endoscopic approach for sellar tumors, with preservation of the nasoseptal flap and selective mobilization for reconstruction. Methods A retrospective case-control study was performed comparing the Hemi-T approach with previously used methods of sellar exposure and reconstruction. Outcome measures included operative time and postoperative nasal morbidity. Results A total of 23 patients underwent the Hemi-T approach versus 42 in whom traditional exposure was performed. Operative time was significantly shorter using the Hemi-T technique (152.6 ± 56.8 versus 205.2 ± 61.3 minutes; p = 0.001), as was the length of hospital stay (3.3 ± 1.9 versus 5.4 ± 3.6 days; p = 0.004). There was no difference in the rates of intraoperative or postoperative cerebrospinal fluid leak, cartilage necrosis, septal perforation, or mucosal adhesions. Conclusion The Hemi-T approach facilitates binasal two-surgeon access to the sella without compromise of the pedicle during the extended sphenoidotomies and tumor removal. Operative time and nasal morbidity is not increased, and iatrogenic injury to the nasal cavity is minimized when a flap is not required.